Formulasi orally disintegrating tablet dari serbuk kembang kol (Brassica oleracea var. botrytis L.) dengan variasi konsentrasi sari tapai sebagai disintegrant - Lestari, Sri Indah; Dalimunthe, Gabena Indrayani; Lubis, Minda Sari; Nasution, Haris Munandar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Cauliflower (Brassica oleracea var. botrytis L.) has a nutritional content consisting of calcium, magnesium, potassium, phosphorus, and low saturated fat. It has vitamin C, which helps increase body immunity. Orally Disintegrating Tablet preparations can dissolve quickly when placed on the tongue, formulated for ease of use of drugs for patients who have difficulty swallowing. Therefore, disintegrants are very important in ODT preparations. Tapai extract has a sweet, slightly sour taste and disintegrates immediately when placed on the tongue. This research aimed to determine whether cauliflower powder with tapai extract disintegrants can be formulated into ODT preparations and which formulation is the best. This research included characterization of simplicia, making pre-formulation by mixing all ingredients, evaluating pre-formulation, and tablet printing by direct compression method. Then, the tablet evaluation was carried out. The disintegrant was tapai extract with 5%, 7.5%, and 10% concentrations. Data were analyzed using the One Way ANOVA method. The results of the formulation evaluation, the flow time test obtained <10 seconds, which is easy to flow; the angle of repose test obtained 26˚, the category is very good; and the compressibility test obtained 18-20%, which is quite good. The results of the tablet evaluation in the organoleptic test obtained round tablets, sweet taste, brownish-white color, and distinctive odor. The weight uniformity test on all formulas did not have any deviating weights; the size uniformity test met the requirements, the hardness test obtained 1-3 kg, the friability test obtained 0.4-0.7%, the petri dish disintegration time test obtained 44.07-52.48 seconds, and the mouth disintegration time test obtained 53.07-57.78 seconds and the wetting time test obtained 53.21-54.87 seconds. The best formula is formula 3, with a 10% tapai extract concentration.